THE EFFECT OF GOVERNMENT SUPPORT, PARTICIPATION OF MEMBERS, MANAGER’S PERFORMANCE, AND ACCESS TO CAPITAL SOURCES ON THE PERFORMANCE OF COOPERATIVES, ECONOMY AND WELVARE OF THE MEMBERS IN THE CITY OF TOURIST BATU EAST JAVA INDONESIA. - kyai, burhan (Archives of Business Research, 2019)
ABSTRACT An interesting thing of Batu City is the acceleration of its growth, which, during the last 12 years, has become the third most visited city by Asian tourists, after Bali and the Special Region of Yogyakarta. Batu City has a special character that is different from other cities, namely the beautiful atmosphere of the mountains, the cool air, lush with fruits, vegetables, flowers, and agricultural and livestock products. Starting from 6 tourist attractions now it has had more than 40 tourist destinations so that it becomes very popular. However, the growth of Batu City has not been accompanied by the economic growth of its people, resulting in a gab between what is expected and what is real. The purpose of this research is to analyze, test, prove and evaluate the influence of independent variables of Government Support, Member Participation, Manager Performance, and Access to Capital Resources on the dependent variables namely Cooperative Performance, Member Economy and Member Welfare. The knowledge of the influence of the tested variables on the progress of cooperatives is helpful for evaluating the performance of cooperatives in order to improve the economy and the welfare of cooperative members in general. This research is an explanatory study through hypothesis testing. By using 2 versions of the statistical analysis, namely Regression Analysis and Structural Equation Modeling (SEM). SEM is needed to find out more in detail about the various factors / variables and find the most dominating indicators of the progress of the cooperative.The results of the analysis based on the Regression Test state that all 6 variables under study have a significant effect; moreover, Partial/Equivalent Tests find similar results. Furthermore, the Structural Modeling Test indicated that the 7 variables being studied were good. The hypothesis testing using Weigh Regression proves that the 7 hypotheses proved to be significantly influential. The Loading Factor analyses showed a significant effects of: 1) Government Support (Variable D) with a significance value of 0.034 (p<0.05); 2) Member Participation (Variable A) with a significance value of 0.049 (p<0.05); 3) Manager Performance (Variable M) with a significance value of 0.046 (p<0.05); 4) Capital Access (Variable U) with a significance value of 0.036 (p<0.05); 5) Cooperative Performance (Variable K) with a significance value of 0.028 (p<0.05); 6) Member Economy (Variable EA) with a significance value of 0.028 (p<0.05); 7) and Member Welfare (Variable P) with a significance value of 0,000 (p<0.05). Thus, all of the seven proposed hypotheses proved to be confirmed. It implies that those seven variables significantly influence the progress of cooperatives; therefore, they can be used to study, analyze, evaluate and innovate the development of cooperatives in Batu Tourism City. If the cooperative is strong, the economy and the welfare of the members will automatically increase. Keywords : cooperative, economy, welfare